WEBBING TECHNIQUE TO IMPROVE THE STUDENTS´ WRITING RECOUNT - Ariana Ariana (Universitas Muhammadiyah Makassar, 2015)
This research was aimed at investigating the use of webbing technique in teaching writing recount text. A quasi experimental design was employed with two classes of the eleventh graders at one school in Sungguminasa, Gowa selected with cluster sampling as sample. The data were obtained through a pre-test, a post-test and an questionnaire. The writing assessment was covering content, schematic structure, and language use. The findings were analyzed statistically using independent t-test procedure. The statistical computation showed that webbing technique was likely effective in improving the students’ writing skill in recount text (value of t 6,74value of t table1,99). Furthermore, the students´ perception towards webbing technique is 91,7% students agree that this technique could help them to increase their writing skill. Designing the learning purpose appropriately which considers students’ needs and language level may ease teachers to use the webbing technique in improving students’ writing recount text. The teachers may try to take advantage of webbing technique to be utilized in their classroom activities to conduct an effective and interesting learning atmosphere in the classroom.